2009
DOI: 10.1242/dev.035592
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between activin and Hox genes determines the formation of the kidney morphogenetic field

Abstract: The kidney develops in a specific position along the anterior-posterior axis. All vertebrate kidney tissues are derived from the intermediate mesoderm (IM), and early kidney genes such as Lim1 and Pax2 are expressed in amniotes posterior to the sixth somite axial level. IM cells anterior to this level do not express kidney genes owing to changes in their competence to respond to kidneyinductive signals present along the entire axis. We aimed to understand the molecular mechanisms governing the loss of competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 57 publications
5
41
0
Order By: Relevance
“…Although the focus and theme of this article is Hox gene expression in early stages of kidney field specification, we also describe the kinetics of the expression of these genes in other mesodermal tissues. This is particularly important as several previous studies, including studies from our lab, show the crucial effect of neighboring tissues on IM specification at early developmental stages and the establishment of the kidney morphogenetic field (Mauch et al, 2000;Obara-Ishihara et al, 1999; and Schultheiss, 2003Barak et al, 2005;Preger-Ben Noon et al, 2009).…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Although the focus and theme of this article is Hox gene expression in early stages of kidney field specification, we also describe the kinetics of the expression of these genes in other mesodermal tissues. This is particularly important as several previous studies, including studies from our lab, show the crucial effect of neighboring tissues on IM specification at early developmental stages and the establishment of the kidney morphogenetic field (Mauch et al, 2000;Obara-Ishihara et al, 1999; and Schultheiss, 2003Barak et al, 2005;Preger-Ben Noon et al, 2009).…”
Section: Introductionmentioning
confidence: 78%
“…Preger-Ben Noon et al (2009) have demonstrated the role played by Hoxb4 in conferring the competence of IM cells to respond to activin-like signals emanating along the entire axis (including non-kidney IM) from the dorsal neural tube to induce early kidney genes. Because this gene exhibits an anterior expression boundary at the sixth somite level, it was suggested that the lack of Hoxb4 in anterior IM tissue attributes to the loss of kidney gene expression in this region despite the presence of kidneyinductive signals (Barak et al, 2005;Preger-Ben Noon et al, 2009). If this is correct, then the position of the pronephros along the IM A-P axis can be considered to be Hoxb4-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations